2011
DOI: 10.1097/tp.0b013e318204756c
|View full text |Cite
|
Sign up to set email alerts
|

miRNA Regulation of Liver Growth After 50% Partial Hepatectomy and Small Size Grafts in Rats

Abstract: Background. The molecular mechanisms underlying the growth of small size grafts and the remaining livers are poorly understood. MicroRNAs (miRNAs) negatively modulate expression of genes that are involved in cellular function and metabolism. The aim of this study is to identify critical miRNA species that modulate the growth of small grafts and the remaining livers after partial hepatectomy (PH). Methods. Small size graft liver transplantation was performed in rats. Liver tissue was harvested after transplant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 24 publications
3
37
0
Order By: Relevance
“…Using a similar approach as Cirera-Salinas et al, they treated mice with miR-26a mimics and oligonucleotides and showed that artificial downregulation of miR-26a enhanced hepatocyte proliferation (1.2fold increase of Ki-67 positive cells compared to controls) and induced upregulation of the potential targets cyclin D2 and cyclin E2. Chen et al had already shown that overexpression of miR-26a down-regulated cyclin E2 protein levels and significantly decreased proliferation of HepG2 cells [65]. Similar results with regard to induction of hepatocyte proliferation were obtained by Pan et al for miR-127 [66], which was observed to be downregulated 3 and 24 h after partial hepatectomy in rats.…”
Section: Hepatocytessupporting
confidence: 85%
“…Using a similar approach as Cirera-Salinas et al, they treated mice with miR-26a mimics and oligonucleotides and showed that artificial downregulation of miR-26a enhanced hepatocyte proliferation (1.2fold increase of Ki-67 positive cells compared to controls) and induced upregulation of the potential targets cyclin D2 and cyclin E2. Chen et al had already shown that overexpression of miR-26a down-regulated cyclin E2 protein levels and significantly decreased proliferation of HepG2 cells [65]. Similar results with regard to induction of hepatocyte proliferation were obtained by Pan et al for miR-127 [66], which was observed to be downregulated 3 and 24 h after partial hepatectomy in rats.…”
Section: Hepatocytessupporting
confidence: 85%
“…miRNAs are responsible for a number of physiological processes, including cell growth/differentiation and maintenance of internal environmental stabilization [5]. miRNAs are also necessary for sustaining hepatic function [6], controlling hepatocyte proliferation [7] and regulating liver development [8]. Deregulated expression of miRNAs, however, contributes to the development of a number of liver diseases, e.g., miR-122 is implicated in the facilitation of HCV replication [9].…”
Section: Introductionmentioning
confidence: 99%
“…Western blot assays were performed as reported previously. 39 In brief, equal amounts of protein samples were loaded and separated by 10-12% Tris-Glycine Ready Gel (Invitrogen) and the protein in the gel was transferred to a polyvinylidene fluoride membrane (Novex, Invitrogen). For antibody blotting, the membranes of the nuclear protein were incubated with polyclonal anti-Gli-1 (Santa Cruz Biotechnology, Inc., Santa Cruz, CA, USA), anti-Gli-2 (Abcam, Cambridge, MA, USA) and polyclonal anti-Twist (Santa Cruz Biotechnology, Inc.) in Trisbuffered saline containing 1% BSA for overnight at 4 ℃.…”
Section: Ts Cells and Invasion Assaymentioning
confidence: 99%